Letter (copy) : International Solidarity Fund: field ambulance - Citrine, Walter, 1887-1983
041-0033-001 WMC/WJP/AC/602[3] International 12th April, 1937 Mr. A. Naesmith, Amalgamated Weavers' Association, Ewbank Chambers, 19, St. James St., ACCRINGTON. Dear Mr. Naesmith, INTERNATIONAL SOLIDARITY FUND. FIELD AMBULANCE. With further reference to your letter of 25th ultimo, we have today heard from Mr. Schevenels to the effect that he has ordered a field ambulance with equipment and stretchers, which will be despatched immediately for operation in connection with the base hospital which has been set up by the International Solidarity Fund at Onteniente in Spain. He wishes me to say how deeply grateful the International Solidarity Fund Committee are for this generous and practical gesture on the part of the members of the Amalgamated Weavers' Association. He adds that it is intended to affix a tablet to the ambulance indicating from whom the gift was received. As soon as I can obtain a photograph of this, I will send it to you. Yours faithfully, General Secretary. 292/946/41/33